Psykiatrisessa hoidossa olleen nuoren aikuisen kokemuksia elämästään ja elämää eteenpäin vievistä asioista = Experiences of life and of things making life worth living as experienced by the young adult who has been in psychiatric care - Kiviniemi, Liisa (Kuopion yliopiston julkaisuja, 2008)
Abstract: Experiences of life and of things making life worth living as experienced by the young adult who has been in psychiatric care.
Keywords: Adolescent; Life Change Events; Life Style; Mental Disorders; Mental Health; Psychiatric Nursing; elämänhistoria; elämänodotukset; fenomenologia; kokemukset; mielenterveyshäiriöt; nuoret; psykiatrinen hoito; psykiatriset potilaat